Prevalence and Management Issues Associated with Poultry Coccidiosis in Abak Agricultural Zone of Akwa Ibom State, Nigeria - Etuk, E.B.; Okoli, I.C.; Uko, M.U. (International Journal of Poultry Science, 2004)
A study of six farms each randomly selected from each of five local government areas of Abak agricultural zone of Akwa Ibom State, Southeastern Nigeria, was conducted to assess on-farm prevalence and management of poultry coccidiosis. The study, which involved scrutiny of farm and clinical records, distribution of structured and pre-tested questionnaires to elicit relevant data, showed that in the previous 12 months, 3,327 (29.36%) birds out of 11,333 encountered in the 30 farms suffered from coccidiosis. Overall mortality rate was 2.63%. The highest prevalence rates were recorded in the rainy season (12.7%), among birds managed in deep litter (26.69%), birds 1-5 weeks old (18.75%), layers (22.29%) and Harco strain (26.42%). Sixty percent of the farms consulted veterinarians for diagnosis and treatment especially at first incidence while 34.94% indulged in self-diagnosis. Good sanitary and hygiene practices were being employed in 50% of the farms as the major preventive measure. Combined administration of anticoccidial drugs and removal of litter (43.33%) ranked highest as control measure. Continued veterinary education and extension services are needed in the area to update the knowledge of the farmers especially on the benefits of vaccination, dangers of self-diagnosis and adoption of an integrated approach involving good hygienic practices and use of both drugs and vaccines in disease prevention.